Operationalizing physical literacy through sport education - Peter A. Hastie; Tristan L. Wallhead (Elsevier, 2015)
Physical literacy (PL), as embodied within physical education (PE), has been vaunted as having increasing importance as a disposition for students of all abilities to establish lifelong adherence to physical activity. The purpose of this paper was to provide a discussion of how the pedagogical features of a contemporary pedagogical model, Sport Education (SE), may be used to operationalize PL in PE and what empirical evidence currently exists to validate this claim. Substantial empirical evidence exists that the attributes associated with the development of PL (Whitehead, 2010) can be operationalized in PE with the effective implementation of the model. SE has distinct pedagogical features which positively contribute to many of the dimensions of PL and can further an individuals' journey towards greater PL and having an embodied self within PE. That stated, there remains concern that the context for this embodiment remains too narrow to be viewed as a panacea for the development of lifelong physical activity. SE must be developed as a connective specialism if these PL attributes are to transform the motivation and confidence for individuals to capitalize on their innate physical potential and make a more significant contribution to the quality of life.